Taxonomy and biology of a new ambrosia gall midge Daphnephila urnicola sp. nov. (Diptera: Cecidomyiidae) inducing urn-shaped leaf galls on two species of Machilus (Lauraceae) in Taiwan - Pan, Liang-Yu; Chiang, Tung-Chuan; Weng, Yu-Chu; Chen, Wen-Neng; Hsiao, Shu-Chuan; Tokuda, Makoto; Tsai, Cheng-Lung; Yang, Man-Miao (Zootaxa, 2015)
Recent field surveys show that galls induced by Daphnephila spp. (Cecidomyiidae) on Machilus spp. (Lauraceae) are common in Taiwan, yet only five species, four leaf-gall inducers and one stem-gall inducer on M. thunbergii, have been named in the past. Here we describe a new species, Daphnephila urnicola sp. nov. Chiang, Yang & Tokuda, inducing urn-shaped galls on leaves of both M. zuihoensis and M. mushaensis. Comparisons of D. urnicola populations on M. zuihoensis and on M. mushaensis, indicate that they belong to one species, a result supported by gall midge morphology, life-history traits, gall shape and structure, the developmental process of gall tissues, fungal associations, and DNA-sequencing data. Size and structure of the gall operculum was found to differ between M. zuihoensis and M. mushahaensis.